FAKTOR-FAKTOR PELUANG PADA PERUSAHAAN PERUSAHAAN YANG TERKENA DAMPAK KRISIS GLOBAL - Nina Rostina (JURNAL EKOMBIS, 2018)
This research examines what factors that can increase a company’s survival probability. Thirty financial distress companies in the years 1997-2005 with insolvency type were observed. At the end of 2005, as much as 53,33% companies could survive as an independent company. The data were examined relying on logistic regression. The covariates are operating performance, president director turnover, company’s age, and creditor equity stake. The dependent variable is the company status. Survival is positively affected by its operating performance. The only other factor systematically increasing company’s survival probability is the willingness of creditors to take an equity stake in the companies. Almost of all creditor equity stake in financially-distressed companies was executed by foreign creditor. President director turnover when the distress and company’s age did not increasing company’s survival. Keywords: survival probability, financial distress, and creditor equity stake